Een trouwe vriend van Hongarije: Ds. Han Munnik (1884–1969) - Aalders, Maarten J. (Acta Neerlandica, 2021)
From 1921 on, the Reformed Churches in the Netherlands had a study fund, especially for Hungarian students. Until the Second World War, about 40 students studied with funding from that scholarship, neatly distributed between the Free University and the Theological School in Kampen. The chairman of the fund was Prof. F.W. Grosheide (1881–1972) of the Free University, its secretary was Rev. H.A. Munnik (1884–1969), from Zwolle. Both were involved in the fund from 1921 on, Grosheide retired in 1952, Munnik a few years later. Munnik became an honorary member of the Association of Hungarian Pastors and Honorary Professor in Debrecen (1938), Grosheide became Honorary Doctor in Sárospatak (1931), Debrecen (1938), and Budapest (1946). This indicates their significance for the Hungarian ministerial corps and for the contacts between Hungary and the Netherlands in those years.